2022
DOI: 10.1155/2022/4955209
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive In Silico Analysis of RNA Silencing‐Related Genes and Their Regulatory Elements in Wheat (Triticum aestivum L.)

Abstract: Dicer-like (DCL), Argonaute (AGO), and RNA-dependent RNA polymerase (RDR) are known as the three major gene families that act as the critical components of RNA interference or silencing mechanisms through the noncoding small RNA molecules (miRNA and siRNA) to regulate the expressions of protein-coding genes in eukaryotic organisms. However, most of their characteristics including structures, chromosomal location, subcellular locations, regulatory elements, and gene networking were not rigorously studied. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 133 publications
2
3
0
Order By: Relevance
“…TaAGO18 subfamily was aligned with Z. mays and O. sativa. AGO18 ortholog proteins in the phylogenetic study, suggesting that both had comparable activities, similar results were reported in prior reports [32,33] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…TaAGO18 subfamily was aligned with Z. mays and O. sativa. AGO18 ortholog proteins in the phylogenetic study, suggesting that both had comparable activities, similar results were reported in prior reports [32,33] .…”
Section: Discussionsupporting
confidence: 91%
“…However, there are slight variations between the TaDCL and their orthologues: (1) While rice and maize DCL1 PAZ and Dicer-dimer domains alter somewhat from those of TaDCL1, TaDCL1's domain organization is extremely similar to that of AtDCL1. This change may have taken place following the split between the rice and maize ancestor and the common ancestor of wheat and barley (roughly 60 million years ago) [14]; (2) the PAZ domain in monocot DCL2s (including wheat and barley) may have a modified structure, indicating a different folding and RNA binding [32,36]; and (3) upon analysis, we discovered a highly conserved DCL catalytic core within all DCLs (Figure 2b). Although dsRNA binding may change between DCL orthologs and paralogs, (4) unlike dicots, monocots have developed a fifth DCL, DCL5 [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The 11 ClRDR proteins were divided into four clades. Among the four groups, group I contained seven members, named ClRDR1a, ClRDR1b, ClRDR1c, ClRDR1d, ClRDR1e, ClRDR1f, and ClRDR1g (Figure S2b), which is consistent with the number of RDR1 proteins found in Triticum aestivum (Akond et al, 2022). However, four RDR1 proteins were identified in strawberry, which were also diploid (Jing et al, 2023), we speculate that this difference may be due to variation among different species.…”
Section: Resultssupporting
confidence: 81%
“…To date, several studies have shown that the sizes of AGO , DCL , and RDR gene families vary among species. For example, Arabidopsis 14 , rice 15 , maize 16 , millet 17 , grapevine 18 , tomato 19 , wheat 20 , soybean 21 , pepper 22 , cucumber 23 , barley 24 , sugarcane 25 , sweet orange 6 , and tea 26 genomes encode ten, 19, 18, 19, 13, 15, 39, 21, 12, seven, 11, 21, eight, and 18 AGO genes; four, five, five, eight, four, seven, seven, seven, four, five, five, four, four, and five DCL genes; six, eight, five, 11, five, six, 16, seven, six, eight, seven, 11, four, and nine RDR genes, respectively. These studies have also shown that these gene families are highly conserved in plants, although little is known about the corresponding genes in quinoa.…”
Section: Introductionmentioning
confidence: 99%